(untitled) (International Journal of Engineering and Computer Science, 2024)
Artificial intelligence (AI) technology in the oil and gas sector is set to tackle significant issues, including environmental sensitivity and intricate production procedures. Recent breakthroughs in artificial intelligence have enabled the digital transformation and intelligent enhancement of petroleum firms. This article examines the developmental patterns of AI technology, emphasizing its applicability in the oil and gas industry. We evaluate AI technology implementation in domestic and foreign petroleum technology service organizations by evaluating industry features and business circumstances. The principal application domains of AI in the oil and gas sector are: dynamic reservoir analysis, sophisticated history matching, numerical simulation proxy modeling, and optimization of production plans. We underscore the need to dive into the issues encountered in developing oil and gas reservoirs by promoting advances in data standards, intelligent oil field management, and collaborative platforms. The "three modernizations" are essential for sophisticated study and management of reservoirs, enabling the rapid formulation of focused development plans. The article examines the future possibilities of AI technology, emphasizing the growing need for AI in developing digital oil fields in China. The results provide critical insights for the continuous digital transformation of oil and gas sector, highlighting AI substantial impact on improving operational efficiency and sustainability.